Space Security Law - Abeyratne, Ruwantissa; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Against the variegated background of bewilderment and cautious optimism that space transportation offers, this book begins with an exposé on international politics, the principles of which, bear upon space transportation, as well as the closeness of air space and outer space, and activities that straddle both frontiers at the same time. It discusses current issues and possibilities of communications and transportation in outer space, as well as the liabilities and accountability of the key players of space exploration.
Keywords: Law; Astronautics; Law; Law of the Sea, Air and Outer Space; Aerospace Technology and Astronautics